Konsep Inkarnasi sebagai Pemulihan Kodrat Manusia Menurut Cyril of Alexandria - Rando Kedede (STT INTI Bandung, 2022)
The peculiarity of Cyril's doctrine of incarnation lies in the explanation of specific concepts. While many theologians only see the incarnation as penance, Cyril sees the incarnation as the key to the work of salvation. This means that the incarnation is the first step of the work of penance. On this basis he later stated that the incarnation as a restoration of nature. The work of penance does not stop at the stage of incarnation. Because the culmination of penance is the death and resurrection of Christ. The incarnation restored nature, Christ's death overcame sin, and Christ's resurrection overcame death. Then starting from this concept, Cyril is more specific in his concept by referring to kenosis, Emmanuel, one person, two natures, and recapitulation/Jesus as the second Adam. Through the incarnation, Christ has provided and given a new nature for us to use towards theosis. And it is our free will that determines whether or not to wear the new Christ-given nature.